Airport-driven cityspaces: redefine cityscape of Malaysia by Introducing airport into urban areas - Ru, Koh Yen; Zairul, Mohd; D’Silva, Jeffrey Lawrence
The aviation industry is becoming one of the greatest economic growth drivers in nations and arguably an indispensable form of transport. Airports are already built up around population centers and are already operating at high capacity. And aviation is now going beyond mobility between continents and cities “ it is starting to impact mobility within cities. Despite that, the distance between city and airport may be in the line of slowing down the evolution of airport. Thus, introducing airport into urban areas by challenging the notion of airport development towards verticality to sustain the ever-expanding behavior and redefine cityscapes of Malaysia. In order to understand and imagine the potential changes that could be made to the city airport's development while supporting the always changing, explosive activities, and providing a seamless connection to the urban sphere, interviews and phenomenological research will be conducted. By understanding the factors and variables of city airport in formulating scenarios, which will be adjusted and applied towards its dynamic and demand. Future research can add more variables to planning towards verticality: pro-active urban designs that are developed from alternative expansions.